Adoniram Judson: A dialectical missionary who brought the Gospel (not God) and gave the Bible to the Burmese. Issue 3 (July 2017) - Moe, David Thang
Adoniram Judson (1788–1850) was an American Baptist missionary. His Burmese name was Yuhdathan . His coming to Myanmar "was not originally intentional, but it was providentially accidental" (American Baptist Foreign Mission Society, 1923: 16). This article will read Judson as a dialectical 1 missionary because of his negative view of Buddhism as a false religion, and yet his use of Buddhist religious terms for translation of the Burmese Bible. I will also argue that Judson did not bring God to Myanmar because God has already been there prior to his coming. Rather, he brought the foreign Gospel and gave the Bible to the Burmese. This article is written from a twofold perspective: to offer a description of Judson's mission work, and to offer a prescription of how Judson's success should be appreciated and his failure should be appropriated in a post-Judson age.